Engineered Scaffolds and Cell-Based Therapy for Periodontal Regeneration. Issue 4 (2017) - Carmagnola, Daniela; Tarce, Mihai; Dellavia, Claudia; Rimondini, Lia; Varoni, Elena M.
Background: The main objective of regenerative periodontal therapy is to completely restore the periodontal tissues lost. This review summarizes the most recent evidence in support of scaffold- and cell-based tissue engineering, which are expected to play a relevant role in next-generation periodontal regenerative therapy. Methods: A literature search (PubMed database) was performed to analyze more recently updated articles regarding periodontal regeneration, scaffolds and cell-based technologies. Results: Evidence supports the importance of scaffold physical cues to promote periodontal regeneration, including scaffold multicompartmentalization and micropatterning. The in situ delivery of biological mediators and/or cell populations, both stem cells and already differentiated cells, has shown promising in vivo efficacy. Conclusions: Porous scaffolds are pivotal for clot stabilization, wound compartmentalization, cell homing and cell nutrients delivery. Given the revolutionary introduction of rapid prototyping technique and cell-based therapies, the fabrication of custom-made scaffolds is not far from being achieved.